2009
DOI: 10.1261/rna.1589109
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial tRNA import in Trypanosoma brucei is independent of thiolation and the Rieske protein

Abstract: Due to a complete lack of the tRNA genes in the mitochondrial genome of Trypanosoma brucei, all tRNAs needed for mitochondrial translation have to be imported into the organelle from the cytosol. A previous study showed that the modified nucleotide s 2 U could act as a negative determinant for mitochondrial tRNA import in another kinetoplastid, Leishmania tarentolae. We have investigated whether the same type of cytosolic control for tRNA retention exists in T. brucei. Based on Northern analysis with subcellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 43 publications
(63 reference statements)
3
25
0
Order By: Relevance
“…They were able to show that ablation of Tb-Nfs1 by RNAi does not change the extent of mitochondrial localization of thio-modified or non-thio-modified trypanosomal tRNAs. Further experiments in the same study showed that a chemically dethiolated tRNA Glu was as efficiently imported into isolated mitochondria as its fully modified counterpart (34). These results are fully consistent with our results and support the conclusion that in T. brucei thio modifications do not act as antideterminants for mitochondrial tRNA import.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…They were able to show that ablation of Tb-Nfs1 by RNAi does not change the extent of mitochondrial localization of thio-modified or non-thio-modified trypanosomal tRNAs. Further experiments in the same study showed that a chemically dethiolated tRNA Glu was as efficiently imported into isolated mitochondria as its fully modified counterpart (34). These results are fully consistent with our results and support the conclusion that in T. brucei thio modifications do not act as antideterminants for mitochondrial tRNA import.…”
Section: Discussionsupporting
confidence: 90%
“…The same conclusion was reached in a recent publication by Paris et al (34). They were able to show that ablation of Tb-Nfs1 by RNAi does not change the extent of mitochondrial localization of thio-modified or non-thio-modified trypanosomal tRNAs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consequently, some, if not all, imported tRNAs have two sets of modifications. A typical tRNA destined for the mitochondrion receives some modifications in the nucleus after transcription, additional modifications in the cytosol, and then more modifications following import into the mitochondrion (Paris et al 2009;Phizicky and Alfonzo 2010). This then implies that in common with organisms that encode most or all of their mitochondrial tRNAs in the organellar genome, T. brucei still imports a subset of nucleus-encoded modification enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was made in T. brucei using enzymatic sequencing of tRNA Lys , tRNA Leu , and tRNA Tyr , each of which bears a mitochondrion-specific ribose methylated cytidine residue at position 32 (C m 32) of the anticodon (Schneider et al 1994a,b). Likewise, thiolation of tRNAs has been implicated as a negative determinant for tRNA import in the parasitic flagellate Leishmania tarentolae (Kaneko et al 2003), but the same is not true in T. brucei (Paris et al 2009). …”
Section: Introductionmentioning
confidence: 99%